Feasibility, acceptability and potential effectiveness of an information technology-based, pharmacist-led intervention to prevent an increase in anticholinergic and sedative load among older community-dwelling individuals. (January 2019) - van der Meer, Helene G.; Wouters, Hans; Teichert, Martina; Griens, Fabiënne; Pavlovic, Jugoslav; Pont, Lisa G.; Taxis, Katja
Background: Anticholinergic/sedative medications are frequently used by older people, despite their negative impacts on cognitive and physical function. We explore the feasibility, acceptability and potential effectiveness of an innovative information technology (IT)-based intervention to prevent an increase in anticholinergic/sedative load in older people. Methods: This was a prospective study in 51 Dutch community pharmacies. Pharmacists used an IT-based tool to identify patients aged ⩾65 years, with existing high anticholinergic/sedative loads (drug burden index ⩾2) and a newly initiated anticholinergic/sedative medication. We determined the following. Feasibility: number of eligible patients identified. Acceptability: pharmacists' satisfaction with the intervention, pharmacists' time investment and patients' willingness to reduce medication use. Potential effectiveness: number of recommendations, rate of agreement of general practitioners (GPs) with proposed recommendations and factors associated with agreement. To evaluate the latter, pharmacists conducted medication reviews and proposed recommendations to GPs for 5–10 patients selected by the IT-based tool. Results: We included 305 patients from 47 pharmacies. Feasibility: a mean of 17.0 (standard deviation, 8.8) patients were identified per pharmacy. Acceptability: 43 pharmacists (91.5%) were satisfied with the intervention. The median time investment per patient was 33 min (range 6.5–210). Of 35 patients, 30 (85.7%) were willing to reduce medication use. Potential effectiveness: pharmacists proposed 351 recommendations for 212 patients (69.5%). GPs agreed with recommendations for 108 patients (35.4%). Agreement to stop a medication was reached in 19.8% of recommendations for newly initiated medications (37 of 187) and for 15.2% of recommendations for existing medications (25 of 164). Agreement was more likely for recommendations on codeine [odds ratio (OR) 3.30; 95% confidence interval (CI) 1.14–9.57] or medications initiated by a specialist (OR 2.85; 95% CI 1.19–6.84) and less likely for pharmacies with lower level of collaboration with GPs (OR 0.15; 95% CI 0.02–0.97). Conclusion: This innovative IT-based intervention was feasible, acceptable and potentially effective. In one-third of patients an increase in anticholinergic/sedative load was prevented within reasonable time investment.